Design and synthesis of small molecule modulators of p53 - Ribeiro, Carlos Jorge Azevedo Costa, 1980- (2018)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2015